Contrast-enhanced magnetic resonance imaging (MRI) features of Gruberi Bursitis as a very rare cause of dorsolateral ankle pain and swelling: Case report and review of the literature - Yasser Ragab, MD, PhD; Yasser Emad, MD, PhD; Mariam Ahmed Saad, MD, MSc; Johannes J. Rasker, MD PhD (Radiology Case Reports, 2022)
The Gruberi sinus tarsi bursa is a dorsolateral ankle anatomic bursa that has been described in the past but is rarely mentioned in recent radiology literature. The Gruberi bursa is distinguished by its position between the extensor digitorum longus tendons and the talus. It is usually unilocular, anechoic and compressible as shown with ultrasound in a previous study. In recent literature, the enhanced MRI features of an inflamed Gruberi bursa as the underlying cause of a painful ankle joint and antalgic gait are rarely demonstrated. In this report, we present the enhanced MRI features of Gruberi bursitis in a female patient who complained of acute onset of pain and swelling along the dorsolateral aspect of her left ankle, as well as a painful limping gait after sport-related activities. Complaints improved after an intra-bursal corticosteroid injection. The case is discussed and the typical enhanced MRI features are demonstrated. The relevant literature is discussed.